Effectiveness of a peer group-based online intervention program in empowering families of children with disabilities at home - Wakimizu, Rie; Matsuzawa, Akemi; Fujioka, Hiroshi; Nishigaki, Kaori; Sato, Iori; Suzuki, Seigo; Iwata, Naoko (Frontiers in Pediatrics, 2022)
The empowerment of families raising children with disabilities is crucial in maintaining their health. We developed an evidence-based, family empowerment intervention program focusing on social resource utilization and reducing care burden. To determine the program’s effectiveness in promoting family empowerment. We compared an intervention group that started the online intervention program a week after initial evaluation and a group that received delayed intervention (waitlist-controlled group) at three timepoints: initial (T1), post-course (T2), and follow-up (T3). The required sample size was 52. There were 60 participants applied to the program. One participant dropped out due to scheduling issues, and the others were assigned to either the intervention group (n = 29) or the waitlist-controlled group (n = 30). Those who responded to the baseline questionnaire (T1: 26 from the intervention group; 29 from the waitlist-controlled group) comprised the final sample. Among them, 20 members of the intervention group and 20 of the waitlist-controlled group attended all four sessions (completion rate 77% and 69%, respectively). The attendance rate for sessions 1–4 was 94%, 89%, 81%, and 83%, respectively. The participant numbers in each session ranged from 5–18 per month. The baseline outcome score did not differ between the groups. The primary outcome, family empowerment, measured using the Family Empowerment Scale (FES), was significantly higher at T2 for the intervention group than the waitlist-controlled group and was sustained in the sensitivity analysis. The intervention group’s FES, in the family relationships (FA) and relationships with service systems (SS) subdomains, increased significantly, unlike involvement with the community (SP). The intervention group experienced lower care burden and higher self-compassion, especially in the isolation and over-identification items of the Self-Compassion Scale–Short Form (SCS–SF). The intervention group’s FES (total, FA, SS) and SCS-SF (total, common humanity, isolation) changed significantly between T1 and T2, and all, except common humanity, were sustained up to T3; this group’s FES (SP) and SCS (negative score, over-identification) changed significantly between T1 and T3. The waitlist-controlled group’s FES (total, FA) and SCS (total) changed significantly and were sustained between T2 and T3.The developed intervention program promotes family empowerment in families of children with disabilities.